2018
DOI: 10.1007/s40271-017-0296-y
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Discrete-Choice Experiments and Conjoint Analysis Studies in People with Multiple Sclerosis

Abstract: Attribute-based stated preference is a useful method with which to examine the preferences of people with MS in their choice of DMT. However, further research embracing the methodological recommendations identified, particularly greater use of qualitative methods in attribute development, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 70 publications
2
44
0
1
Order By: Relevance
“…8,9,11 An additional consideration further complicating treatment decisions is that such treatments are most effective in young patients with RRMS who are not yet affected by high levels of disability but would be exposed to the risk of severe side effects without significant short-term clinical benefit, although with potential long-term slowing of disease progression. 12 Despite the significance of these trade-offs in therapeutic decision making, there is limited research to date that has evaluated the relative importance of various treatment attributes from a patient perspective and how different treatment characteristics may affect treatment choice for patients, particularly in light of the rapidly evolving therapeutic armamentarium for MS. Webb et al 13 reviewed attribute-based stated-preference studies in people living with MS and found 16 studies focusing on DMTs, of which only two used qualitative approaches that involved patients in the development of attributes, with the remaining studies relying on health care professionals and existing medical and social science literature. Given that previous research has highlighted the strengths/needs of using qualitative approaches in the development of attributes to be used in stated preference studies, 14 this qualitative study drew on focus groups of patients with MS to understand their preferences regarding the different characteristics of available and emerging "quite straightforward."…”
Section: Focus Group Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,11 An additional consideration further complicating treatment decisions is that such treatments are most effective in young patients with RRMS who are not yet affected by high levels of disability but would be exposed to the risk of severe side effects without significant short-term clinical benefit, although with potential long-term slowing of disease progression. 12 Despite the significance of these trade-offs in therapeutic decision making, there is limited research to date that has evaluated the relative importance of various treatment attributes from a patient perspective and how different treatment characteristics may affect treatment choice for patients, particularly in light of the rapidly evolving therapeutic armamentarium for MS. Webb et al 13 reviewed attribute-based stated-preference studies in people living with MS and found 16 studies focusing on DMTs, of which only two used qualitative approaches that involved patients in the development of attributes, with the remaining studies relying on health care professionals and existing medical and social science literature. Given that previous research has highlighted the strengths/needs of using qualitative approaches in the development of attributes to be used in stated preference studies, 14 this qualitative study drew on focus groups of patients with MS to understand their preferences regarding the different characteristics of available and emerging "quite straightforward."…”
Section: Focus Group Interviewsmentioning
confidence: 99%
“…Johnson et al 19 to evaluate the benefit-risk trade-offs of treatment attributes associated with natalizumab found that the most important attribute of DMTs for patients with MS was slowing disability progression (in years) and, in fact, they seemed willing to tolerate a nontrivial risk of death for delaying disability progression. Contrary to most previous studies in MS that developed attributes used in stated preference studies by relying on perspectives of health care professionals or existing literature without involving people with MS, 13 this qualitative study drew on the patients with MS focus group discussions to identify preferences regarding the different characteristics of available and emerging drug therapies for MS. In particular, this study provides insights on how patients value noninjectable drug administration relative to effectiveness, side effects, and potential adverse events.…”
Section: Practice Pointsmentioning
confidence: 99%
“…In the context of MS, where PwRRMS have uncertain disease trajectories, understanding of information is important for making informed treatment decisions [13,14] and ensuring that people P treatment preferences and information needs, however, are heterogeneous, change over time and, most importantly, context-dependent [15]. Although several preference surveys have been conducted, qualitative research within them is limited [16]. Specifically, it is not yet understood when PwRRMS prefer to start treatment after diagnosis, why, which type of DMT and how their choices are related to treatment attributes (risks, benefits, side effects, mode of administration, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating these values in decision-making may ultimately result in clinical, licensing, reimbursement, and policy decisions that better reflect the preferences of every stakeholder. However, the methods to assess DMT attributes should be improved, including greater use of qualitative research for attribute/level development, sample size considerations, and design of a stated preference survey [12,26].…”
Section: Discussionmentioning
confidence: 99%
“…One technique of preferences elicitation is conjoint analysis (CA), a multivariate method based on mathematical psychology to evaluate health-related decisions requiring consideration of risks and benefits [24]. CA has been successfully applied to assess preferences for a diverse range of health interventions in different settings [25,26].…”
Section: Methodsmentioning
confidence: 99%